Colonization of wheat grain by Fusaria in two crop management systems varying in intensity of production technology. - Czaban, J.; Wróblewska, B.; Sułek, A.; Podolska, G. (Plant Breeding and Seed Science, 2011)
The purpose of this study was to investigate the effects of two cropping systems (intensive and integrated) on infection level of winter and spring wheat kernels by Fusarium species. Field experiments were conducted with winter wheat ‘Tonacja’ and spring wheat ‘Bombona’ during two consecutive growing seasons (2007/2008 and 2008/2009 - winter wheat, and 2008 and 2009 - spring wheat). A rainfall level in 2009 from the last decade of May to the first decade of July was 2.5-times higher than that in 2008. After the harvest, kernels were surface disinfected with 1.5% NaOCl solution for 2 min and then analysed for the infection level by different species of Fusarium. Fusaria were isolated on CZID medium and identified on the basis of macro - and micro-morphology on three media (PDA, SNA and a medium containing tannin). Our results demonstrate that the wheat grain infection by Fusarium depended mainly on a rainfall level. The intensive cropping system was more conducive to the grain infection by fusaria in comparison to the integrated one. The most frequent species were F. avenaceum in 2008, and F. graminearum, F. avenaceum and F. poae in 2009.